Examining seasonal anomalies in crude palm oil markets - Hisham, M.; Mohd Nor, Normaziah; Li, Wenhui (Inderscience Publishers, 2025)
Crude palm oil (CPO) is a crucial global agricultural commodity, and the efficiency of its market is important for maintaining price stability. This study delves into the assessment of market efficiency in the primary CPO markets, focusing on seasonal anomalies as a key indicator. The research analyses daily, weekly, and monthly data to investigate these anomalies, recognising variations among countries. Our empirical findings reveal significant seasonal anomalies in crude palm oil market. Malaysia and Indonesia exhibit significant day-of-the-week effects, while all four countries demonstrate substantial positive returns during weeks 6 and 52. Notably, Malaysia experiences a significant positive return during October. Furthermore, our research underscores the role of good sentiment around holidays and seasonal export activities as drivers behind these seasonal anomalies. In essence, this study makes a significant contribution to our understanding of market efficiency and the presence of seasonal anomalies in the primary CPO markets. It emphasises the influence of sentiment and export cycles on market returns, providing valuable insights for market participants and policymakers.